Surface geochemical and geophysical studies for geothermal exploration at the southern volcanic rift zone of Tenerife, Canary Islands, Spain. (May 2015) - Rodríguez, Fátima; Pérez, Nemesio M.; Padrón, Eleazar; Melián, Gladys; Piña-Varas, Perla; Dionis, Samara; Barrancos, José; Padilla, Germán D.; Hernández, Pedro A.; Marrero, Rayco; Ledo, Juan José; Bellmunt, Fabián; et al.
Highlights: Soil gas and magnetotelluric surveys were performed in Tenerife Island. The N–S volcanic-rift shows areas of enhanced permeability for deep gas migration. A layer interpreted as the clay cap of the volcano-geothermal system was found. Abstract: A joint geochemistry and magnetotellurics survey was carried out in the southern volcanic rift zone of Tenerife (Canary Islands, Spain) covering an area ∼100 km 2 for geothermal exploration purposes. Soil CO2 and H2 S diffuse effluxes, 222 Rn and 220 Rn activities, soil He, H2, N2, CO2, O2 and H2 S concentrations and isotopic composition of CO2 were measured in 557 selected sampling sites. Magnetotelluric survey (MT) was carried out in the northern part of the study area. A total of 47 MT sites were surveyed and a new 3-D resistivity model was obtained. The observed geochemical anomalies at the soil surface have allowed the detection of areas of deep-seated gas emanations as well as the identification of high vertical permeability volcano-tectonic features in the study area. The resistivity distribution model shows a prominent low-resistivity structure interpreted as a clay alteration cap of variable thickness that might play a role on the mechanism of upward motion of deep-seated gases from the volcano-geothermal system. This is supported by positive correlation between thickness of clay alteration cap and helium emission.